Cytomegalovirus retinitis in non-HIV patients in Chiang Mai University Hospital - Tangthongkum, Siree; Ausayakhun, Somsanguan (Biomedical Sciences and Clinical Medicine, 2023)
Objective To study the associated factor of cytomegalovirus (CMV) retinitis in patients without human immunodeficiency virus (HIV) infection. Design Retrospective case series. Methods A retrospective review of medical records from 12 eyes of 9 consecutive patients with cytomegalovirus retinitis in the absence of HIV infection was conducted at Chiang Mai University Hospital from January 2006 to August 2012. Demographic data, underlying disease and other medical conditions, previous treatment for underlying disease, clinical manifestation and treatment for CMV retinitis were recorded and analyzed for associating factors that increase the risk of CMV retinitis. Results The average age of patients was 53.9 years (SD= 10.26, range 35-65 years). Three patients (33.33%) had bilateral CMV retinitis. The underlying diseases of the patients included systemic lupus erythematosus (n=2, 22.22%), renal insufficiency (n=5, 55.56%), polymiositis (n=1, 11.11%), myasthenia gravis (n=11.11%), cell-mediated immunity (CMI) defect (n=1, 11.11%) and metabolic diseases (n=5, 55.56%). Two patients (22.22%) had renal transplantation, while 8 (88.89%) received immunosuppressive drugs. Two patients (22.22%) had CMV nephropathy and CMV colitis. All of the patients had initial manifestation with visual impairment. Conclusions In the case series of this study, CMV retinitis was observed mostly in patients receiving therapy with an immunosuppressive agent. It was suggested that patients should receive frequent and careful ophthalmic examination of CMV retinitis after initiation of immunosuppressive therapy, and symptomatic patients with clinical signs such as visual impairment should be assessed, as they can indicate manifestations of CMV retinitis.